Super-Fast Drying of blind-holed oil palm lumber (OPL) - Lim, Jia Yuan (2018)
“Super-Fast Drying” method is a newly invented method to dry oil palm wood (OPW). This method involves drilling holes and hot pressing. From the previous study, this method could increase the drying rate of OPW with minimal defects. However, the holing appearance had limited the application of OPW in the industry. In this study, blind holing is introduced with the best holing parameter for both peripheral and core of oil palm trunk were verified. The sample size for core of OPT is cut in the size of (200 x 50 x 18) mm whereas the sample size for peripheral of OPT is (300 x 50 x 18) mm, followed by holes drilling with the depth of 13 , 12 and 23 hole diameter of 5,7 and 9-mm. The specimens were hot pressed and oven dried. Mechanical testing and physical testing were carried out on the sample size with 4 replications. From the findings, both holes’ diameters and holes’ depths result to significant effect on the properties. The optimum holes’ depth and holes’ diameter are 13 and 7-mm respectively.